2020
DOI: 10.1038/s41598-020-79232-y
|View full text |Cite
|
Sign up to set email alerts
|

Divided attention does not affect the acquisition and consolidation of transitional probabilities

Abstract: Statistical learning facilitates the efficient processing and prediction of environmental events and contributes to the acquisition of automatic behaviors. Whereas a minimal level of attention seems to be required for learning to occur, it is still unclear how acquisition and consolidation of statistical knowledge are affected when attention is divided during learning. To test the effect of divided attention on statistical learning and consolidation, ninety-six healthy young adults performed the Alternating Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…In contrast, high-order rule learning could need more attentional resources and consequently occurs only between practice periods. It has indeed been shown during sequence learning that simple transitions 33 , 35 37 , but not more complex structures 38 , could be learned under attentional distraction.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, high-order rule learning could need more attentional resources and consequently occurs only between practice periods. It has indeed been shown during sequence learning that simple transitions 33 , 35 37 , but not more complex structures 38 , could be learned under attentional distraction.…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that statistical learning benefits from evidence accumulation developing during practice and does not consolidate but decays during rest periods. This observation may explain why no evidence for offline consolidation of statistical learning was found during 12-h sleep or awake periods 30 33 .…”
Section: Discussionmentioning
confidence: 99%
“…These RT effects could further increase in ASRT tasks where the acquisition of probabilities is intentional (Nemeth, Janacsek, & Fiser, 2013;Simor et al, 2019;Tóth-Fáber, Janacsek, Szőllősi, Kéri, & Németh, 2020). Meanwhile, in fixed-paced tasks (Kóbor et al, 2020;Tóth et al, 2017) and in those with slow stimulus presentation rate (i.e., long ITI, see Kiss, Nemeth, & Janacsek, 2019;Kóbor et al, 2019), RT effects have been found to be reduced (but see Horváth, Török, Pesthy, Nemeth, & Janacsek, 2020). The present task was fixed-paced, the length of the ITI was longer than previously yielding a slow rate of stimulus presentation, and acquisition occurred incidentally.…”
Section: Interpretation Of Behavioral Resultsmentioning
confidence: 52%
“…To control for the differences in average RTs, we transformed the data in the following way. We divided each participants’ raw RT values of each trial type and each epoch by their own average performance of the first epoch of the task [for a similar approach, see 56 , 57 ], then we multiplied these values by 100 for easier presentation and interpretability. Participants’ performance was around 100 at the beginning of the task and changed as the task progressed.…”
Section: Resultsmentioning
confidence: 99%
“…As typical response times are under 500 ms, the fast pace of the task makes it unlikely that such explicit knowledge would have an impact on participants’ RTs. Therefore, the consciously accessible knowledge of the deterministic serial order of the pattern stimuli (as measured by the post-block sequence report score) and learning of serial-order information (as measured by the RTs) seem to be dissociable measures [ 57 ]. The post-block sequence report may be considered as a more explicit measure of the knowledge on the deterministic serial order of pattern stimuli, while the learning RT scores may serve as an implicit measure of serial-order learning, even in an intentional learning condition.…”
Section: Discussionmentioning
confidence: 99%